SARS-CoV-2 infects cells after viral entry via clathrin-mediated endocytosis - Bayati, Armin; Kumar, Rahul; Francis, Vincent; McPherson, Peter S. (The Journal of biological chemistry, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative agent of COVID-19, so understanding its biology and infection mechanisms is critical to facing this major medical challenge. SARS-CoV-2 is known to use its spike glycoprotein to interact with the cell surface as a first step in the infection process. As for other coronaviruses, it is likely that SARS-CoV-2 next undergoes endocytosis, but whether or not this is required for infectivity and the precise endocytic mechanism used are unknown. Using purified spike glycoprotein and lentivirus pseudotyped with spike glycoprotein, a common model of SARS-CoV-2 infectivity, we now demonstrate that after engagement with the plasma membrane, SARS-CoV-2 undergoes rapid, clathrin-mediated endocytosis. This suggests that transfer of viral RNA to the cell cytosol occurs from the lumen of the endosomal system. Importantly, we further demonstrate that knockdown of clathrin heavy chain, which blocks clathrin-mediated endocytosis, reduces viral infectivity. These discoveries reveal that SARS-CoV-2 uses clathrin-mediated endocytosis to gain access into cells and suggests that this process is a key aspect of virus infectivity.